Quality Attributes of Beef Burger Patties Extended with Soybean Flour and Water melon Seed Cakes - Tibin, I.M.; Mustafa, M. A. (Journal of Veterinary Medicine and Animal Production, 2021)
The study was conducted to determine the effect of blending soybean flour (SF) and watermelon seed cake (WMSC) as meat extenders in the processing of beef burgers. The experiment was composed of five treatments: the control beef meat only, 10% SF, 20% SF, 10% WMSC and 20% WMSC. Several parameters were evaluated using subjective and objective measurements: proximate chemical analysis, pH and water holding capacity, cooking losses, color and sensory evaluation. The fat percentage of the four treatments increased with the level of SF and WMSC; while the control treatment had the lowest fat percentage and the highest cooking losses compared with the other treatments. The 20% WMSC had significantly (P<0.05) the lowest cooking losses and improved WHC. The addition of WMSC resulted in a significant (P<0.05) decrease in cooking losses compared with SF (P<0.05) WMSC was superior to SF in protein and mineral contents, water holding capacity and cooking losses. The color values of the burger were significantly different among treatments (P<0.05). There was a significant improvement in the color, juiciness and tenderness of the extended burger with (P<0.05) and WMSC in comparison with the control. There were no significant difference (P>0.05) between SF and WMSC in color, tenderness and juiciness. However SF was superior to WMSC in flavor and overall acceptability. This study revealed the possibility of adding WMSC as extender in beef burger formulation. However it was almost similar to SF that has been used as extender in burger formulation in different parts of the world. It is recommended to utilize WMSC as extender in ground beef patties formulation with 10% level at this stage